1986
DOI: 10.1128/jb.167.3.837-841.1986
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and purification of the membrane-bound ATPase of the archaebacterium Methanosarcina barkeri

Abstract: Membrane-bound ATPase was found in membranes of the archaebacterium Methanosarcina barkeri. The ATPase activity required divalent cations, Mg2' or Mn2 , and maximum activity was obtained at pH 5.2. The activity was specifically stimulated by HS03-with a shift of optimal pH to 5.8, and N,N'-dicyclohexylcarbodiimide inhibited ATP hydrolysis. The enzyme could be solubilized from membranes by incubation in 1 mM Tris-maleate buffer (pH 6.9) containing 0.5 mM EDTA. The solubilized ATPase was purified by DEAE-Sepharo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 35 publications
1
44
1
Order By: Relevance
“…The presence of this enzyme has been indirectly demonstrated in whole cells of M. barkeri [6,12]. Very recently, Inatomi [13] purified the soluble part of an ATPase from M. barkeri which displays similarities with the F~ part from eubacterial sources: when this Fl-like protein is stripped off the membrane it becomes DCCDinsensitive. However, as long as it is attached to the membrane (probably to the integral F0 part) the ATPase activity is inhibited by DCCD [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this enzyme has been indirectly demonstrated in whole cells of M. barkeri [6,12]. Very recently, Inatomi [13] purified the soluble part of an ATPase from M. barkeri which displays similarities with the F~ part from eubacterial sources: when this Fl-like protein is stripped off the membrane it becomes DCCDinsensitive. However, as long as it is attached to the membrane (probably to the integral F0 part) the ATPase activity is inhibited by DCCD [13].…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Inatomi [13] purified the soluble part of an ATPase from M. barkeri which displays similarities with the F~ part from eubacterial sources: when this Fl-like protein is stripped off the membrane it becomes DCCDinsensitive. However, as long as it is attached to the membrane (probably to the integral F0 part) the ATPase activity is inhibited by DCCD [13]. If this enzyme were involved in proton translocation one would expect DCCD to inhibit the acidification usually observed upon methanol addition.…”
Section: Resultsmentioning
confidence: 99%
“…For protein gel blotting, we used antibodies for two members of PSI complexes (PsaA and PsaB), three members of PSII complexes (PsbB, PsbD, and OEC33;Jain et al, 1998;Jeong et al, 2003), the photosynthetic and respiratory ATP synthase (AtpB; Inatomi, 1986), RbcS (Krebbers et al, 1988), and Lhcb3 (Jackowski et al, 2001). Our data showed that PsaB, PsbD, RbcS, and Lhcb3 proteins were undetectable in the ptac14-1 mutant, while the levels of PsaA, PsbB, and OEC33 proteins were significantly decreased in the ptac14-1 mutant compared with the wild-type plant, and the accumulation of AtpB was less affected in ptac14-1.…”
Section: Chloroplast Development Is Defective In Ptac14 Mutantsmentioning
confidence: 99%
“…They are responsible for vacuolar acidification, which plays an important role in a number of cellular processes (1). V o V 1 -ATPases are also found in the plasma membranes of most archea (7)(8)(9) and some kinds of eubacteria (10 -12). Several studies indicate that the physiological role of V o V 1 -ATPases of some archea and the thermophilic eubacterium Thermus thermophilus is ATP synthesis coupled to proton flux across the plasma membranes (7,9,(13)(14)(15).…”
mentioning
confidence: 99%
“…V o V 1 -ATPases are also found in the plasma membranes of most archea (7-9) and some kinds of eubacteria (10 -12). Several studies indicate that the physiological role of V o V 1 -ATPases of some archea and the thermophilic eubacterium Thermus thermophilus is ATP synthesis coupled to proton flux across the plasma membranes (7,9,(13)(14)(15). Precise understanding of V o V 1 -ATPases would allow the comparison to F o F 1 -ATPases and the elucidation of the common essential mechanism for the coupling of proton translocation across a membrane with ATP formation.…”
mentioning
confidence: 99%